Aging and CMV Infection Affect Pre-existing SARS-CoV-2-Reactive CD8+ T Cells in Unexposed Individuals - Jo, Norihide; Zhang, Rui; Ueno, Hideki; Yamamoto, Takuya; Weiskopf, Daniela; Nagao, Miki; Yamanaka, Shinya; Hamazaki, Yoko (Frontiers in Aging, 2021)
Age is a major risk factor for COVID-19 severity, and T cells play a central role in anti-SARS-CoV-2 immunity. Because SARS-CoV-2-cross-reactive T cells have been detected in unexposed individuals, we investigated the age-related differences in pre-existing SARS-CoV-2-reactive T cells. SARS-CoV-2-reactive CD4+ T cells from young and elderly individuals were mainly detected in the central memory fraction and exhibited similar functionalities and numbers. Naïve-phenotype SARS-CoV-2-reactive CD8+ T cell populations decreased markedly in the elderly, while those with terminally differentiated and senescent phenotypes increased. Furthermore, senescent SARS-CoV-2-reactive CD8+ T cell populations were higher in cytomegalovirus seropositive young individuals compared to seronegative ones. Our findings suggest that age-related differences in pre-existing SARS-CoV-2-reactive CD8+ T cells may explain the poor outcomes in elderly patients and that cytomegalovirus infection is a potential factor affecting CD8+ T cell immunity against SARS-CoV-2. Thus, this study provides insights for developing effective therapeutic and vaccination strategies for the elderly.